The potential of knowledge transfer from universities to the tourism industry in Poland: assessment on the basis of research projects financed by the National Science Centre - Marcin Olszewski (Tourism, 2018)
Knowledge transfer from universities to the socio-economic environment is becoming increasingly important. This challenge also applies to researchers in the field of tourism. The article examines the potential of knowledge transfer, understood as a university’s ability to engage in cooperation with external stakeholders. The aim of this work is to identify this potential on the basis of the number and subjects of research projects qualified for funding by the National Science Center in Poland. According to this study, the number of research grants dedicated to tourism is insufficient. Taking into account the projects, an assessment of knowledge transfer potential is favourable due to the broad scope and relevance of the research.